Gestational and early childhood air pollution exposure and neurodevelopmental outcomes in early childhood - Christina Berninger; Yingying Xu; Patrick Ryan; Kim M. Cecil; Bruce P. Lanphear; Aimée Vester; Kimberly Yolton (Neurotoxicology and Teratology, 2026)

The increasing threat to European forests from the invasive foliar pine pathogen, Lecanosticta acicola - K. Tubby; K. Adamčikova; K. Adamson; M. Akiba; I. Barnes; P. Boroń; H. Bragança; T. Bulgakov; N. Burgdorf; P. Capretti; T. Cech; M. Cleary; et al. (Forest Ecology and Management, 2023)

In Vitro System for Measuring Chordal Force Changes Following Mitral Valve Patch Repair - B. Ostli; J. Vester-Petersen; J. B. Askov; J. L. Honge; R. A. Levine; A. Hagège; S. L. Nielsen; J. M. Hasenkam; H. Nygaard; M. O. Jensen (Cardiovascular Engineering and Technology, 2012)

Mexico's Community‐Managed Forests as a Global Model for Sustainable Landscapes - David Barton Bray; Leticia Merino‐Pérez; Patricia Negreros‐Castillo; Gerardo Segura‐Warnholtz; Juan Manuel Torres‐Rojo; Henricus F. M. Vester (Conservation Biology, 2003)
Researchers concerned with sustainable management of forests in the tropics have argued that the road to improved stewardship of forest resources is the transfer of responsibility to the local communities who get their livelihoods from them. On the other hand, conservationists have declared that the only way to stem the tide of deforestation is to place as many tracts as possible under strict protection. In this context, Mexico presents a national laboratory for studying the social and ecological benefits of delivering forests to local people. As a little‐noticed result of the Mexican Revolution in the second decade of the twentieth century, well over half of the forests of Mexico were placed in community‐held lands. In historic struggles that passed through several phases, most of these communities have now gained substantial control over the use of their forests. Because of the substantial degree of social capital in rural forms of organization in Mexico, this control of forest resources has led to an estimated 290–479 community forest enterprises ( CFEs ), through which communities are producing timber on their own lands. New studies are beginning to suggest that important gains in both social and economic justice, good forest management, and biodiversity protection are resulting from the actions of these CFEs. As more forests globally are being devolved to local communities, it is important to carry out more research on the Mexican model of community forest management for timber production.